2018
DOI: 10.1002/cnm.2970
|View full text |Cite
|
Sign up to set email alerts
|

Effect of KCNQ1 G229D mutation on cardiac pumping efficacy and reentrant dynamics in ventricles: Computational study

Abstract: There is growing interest in genetic arrhythmia since mutations in gene which encodes the ion channel underlie numerous arrhythmias. Hasegawa et al reported that G229D mutation in KCNQ1 underlies atrial fibrillation due to significant shortening of action potential duration (APD) in atrial cells. Here, we predicted whether KCNQ1 G229D mutation affects ventricular fibrillation generation, although it shortens APD slightly compared with the atrial cell. We analyzed the effects of G229D mutation on electrical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Diabetes delays wound healing due to its contribution to the defective regulation of complicated molecular and cellular events in the proper healing process (1). Diabetic foot ulcer (DFU) is one of the most serious diabetic complications that results from poor wound healing, which subsequently results in a major health problem in patients, causing high mortality and disability (2, 3). Diabetic wound healing is involved with multiple complex pathophysiological mechanisms with many extrinsic and intrinsic factors (4).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes delays wound healing due to its contribution to the defective regulation of complicated molecular and cellular events in the proper healing process (1). Diabetic foot ulcer (DFU) is one of the most serious diabetic complications that results from poor wound healing, which subsequently results in a major health problem in patients, causing high mortality and disability (2, 3). Diabetic wound healing is involved with multiple complex pathophysiological mechanisms with many extrinsic and intrinsic factors (4).…”
Section: Introductionmentioning
confidence: 99%
“…Second, we only provide the electrophysiological analysis of the two mutations without considering the mechanical behavior, which previously observed for D172N, G229D, S140G, and V241F mutations. 25 31 32 33 Third, we were unable to compare our simulation results with experimental data due to the limited availability of patients with N588K or L532P mutations. Nonetheless, this computational study demonstrated the relationship between the L532P and N588K mutations with atrial arrhythmia and AF.…”
Section: Discussionmentioning
confidence: 99%
“…From the combination of first and second methods, we performed 96 cases of ventricular tachyarrhythmia simulations. Lastly, we implemented ventricular tachyarrhythmia induced by the following five genetic mutations KCNQ1 S140G (Kharche et al, 2012;Jeong and Lim, 2018), KCNQ1 V241F (Ki et al, 2014;, KCNQ1 G229D (Hasegawa et al, 2014;Yuniarti et al, 2018), hERG L532P, and hERG N588K (Loewe et al, 2014). Thereby, we simulated 20 cases of ventricular tachyarrhythmia according to the types of mutations.…”
Section: Ventricular Tachyarrhythmia Simulation Using Cardiac Excitatmentioning
confidence: 99%
“…There are many cardiac models to elucidate the mechanism of the development and maintenance of tachyarrhythmia and the resulting hemodynamic response (Ten Tusscher et al, 2009;Panfilov et al, 2010). In previous studies, we succeeded in predicting cardiac mechanical responses to various hereditary tachyarrhythmias using the electromechanical-hemodynamic coupling model developed by our research team (Lim et al, 2012(Lim et al, , 2015Choi et al, 2013;Jeong and Lim, 2018;Yuniarti et al, 2018). In this study, we extracted electrical instability features from ventricular tachyarrhythmia simulation.…”
Section: Introductionmentioning
confidence: 99%